Wage and employment effects of immigration to Germany: evidence from a skill group approach - Holger Bonin (Institute for the Study of Labor (IZA), 2005)
The paper analyzes the labor market impact of migration by exploiting variation in the labor supply of foreigners across groups of workers with the same level of education but different work experience. Estimates on the basis of German register data for the period 1975-97 do not confirm the hypothesis that penetration of migrants into skill cells has a significant negative effect on the earnings and employment opportunities of native men. The results indicate that a 10 percent rise of the share of immigrants in the workforce would in general reduce wages by less than one percent and not increase unemployment. Though the adverse effects appear stronger for less-qualified and older workers, the evidence altogether sharply contrasts that from a parallel study for the United States indicating a consistent and substantial negative impact of an immigrant labor supply shock on native competitors.
Keywords: J15; J31; J42; 330; labor market effects of immigration; skill groups; wage elasticity; Germany